Spatio-Temporal Distribution of Chlorophyll-a in Semarang Bay using Sentinel-3 - Muhamad Hafiz Maulavi Haban; Kunarso Kunarso; Teguh Prayogo; Anindya Wirasatriya (Buletin Oseanografi Marina, 2022)
Chlorophyll-a is an indicator for the fertility of waters. The oceanographic conditions make the distribution of chlorophyll-a in waters always changes every season, both spatial and temporal. The aim of this research is to determine the spatial and temporal distribution of chlorophyll-a in Semarang Bay using Sentinel-3 OLCI imagery. Sentinel-3 OLCI imagery has a resolution of 300 m x 300 m, based on the spatial resolution generated by Sentinel-3 OLCI imagery to further examine the spatial distribution of chlorophyll-a in Semarang Bay with better spatial resolution. This research also used wind, current, temperature and salinity data from the Reanalysis Model which were processed using the SNAP program with C2RCC method. It is found that the distribution of chlorophyll-a in the Semarang Bay showed a varied pattern spatially and temporally. Temporally, the highest chlorophyll-a concentration occurred in January and the lowest was in June. Spatially, chlorophyll-a on the coast of Semarang and Demak is higher than that on the coast of Kendal in the west season, but entering the east season the highest chlorophyll-a is on the Kendal coast than on the coast of Semarang and Demak. Chlorophyll-a distribution in Semarang Bay mostly influenced by river run off and wind.